The P2Y2 nucleotide receptor is an inhibitor of vascular calcification. (February 2017) - Qian, Shaomin; Regan, Jenna N.; Shelton, Maxwell T.; Hoggatt, April; Mohammad, Khalid S.; Herring, Paul B.; Seye, Cheikh I.
Abstract: Background and aims: Mutations in the 5'-nucleotidase ecto (NT5E) gene that encodes CD73, a nucleotidase that converts AMP to adenosine, are linked to arterial calcification. However, the role of purinergic receptor signaling in the pathology of intimal calcification is not well understood. In this study, we examined whether extracellular nucleotides acting via P2Y2 receptor (P2Y2 R) modulate arterial intimal calcification, a condition highly correlated with cardiovascular morbidity. Methods: Apolipoprotein E, P2Y2 R double knockout mice ( ApoE − / − P2Y 2 R − / − ) were used to determine the effect of P2Y2 R deficiency on vascular calcification in vivo . Vascular smooth muscle cells (VSMC) isolated from P2Y 2 R − / − mice grown in high phosphate medium were used to assess the role of P2Y2 R in the conversion of VSMC into osteoblasts. Luciferase-reporter assays were used to assess the effect of P2Y2 R on the transcriptional activity of Runx2. Results: P2Y2 R deficiency in ApoE − / − mice caused extensive intimal calcification despite a significant reduction in atherosclerosis and macrophage plaque content. The ectoenzyme apyrase that degrades nucleoside di- and triphosphates accelerated high phosphate-induced calcium deposition in cultured VSMC. Expression of P2Y2 R inhibits calcification in vitro inhibited the osteoblastic trans -differentiation of VSMC. Mechanistically, expression of P2Y2 R inhibited Runx2 transcriptional activation of an osteocalcin promoter driven luciferase reporter gene. Conclusions: This study reveals a role for vascular P2Y2 R as an inhibitor of arterial intimal calcification and provides a new mechanistic insight into the regulation of the osteoblastic trans -differentiation of SMC through P2Y2 R-mediated Runx2 antagonism. Given that calcification of atherosclerotic lesions is a significant clinical problem, activating P2Y2 R may be an effective therapeutic approach for treatment or prevention of vascular calcification. Highlights: P2Y2 receptor deficiency in ApoE − / − mice reduces atherosclerosis. Loss of P2Y2 receptor accelerates arterial intimal calcification in ApoE − / − mice. Expression of P2Y2 receptor inhibits high phosphate-induced smooth muscle cell calcification. P2Y2 receptor negatively regulates Runx2 transcriptional activity in smooth muscle cells.